2021
DOI: 10.1021/acs.analchem.0c05177
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification of Protein Copy Number in Single Cells With Immunofluorescence Microscopy Calibrated Using Single-Molecule Microarrays

Abstract: Great strides toward routine single-cell analyses have been made over the last decade, particularly in the field of transcriptomics. For proteomics, amplification is not currently possible and has necessitated the development of ultrasensitive platforms capable of performing such analyses on single cells. These platforms are improving in terms of throughput and multiplexability but still fall short in relation to more established methods such as fluorescence microscopy. However, microscopy methods rely on fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The SCBC platform was further improved including the expansion of targets, higher throughput, more detection channels, and the simplification of structure . Recently, utilizing green fluorescent protein as a fluorescent, Salehi-Reyhani and colleagues developed an absolute quantification method for intracellular protein in single cells by stoichiometric analysis of single-molecule fluorescence images, and the abundance of a certain protein was determined according to calibrated standard curve . However, the reported microfluidic device-based single-cell analysis requires the professional design of channels, which needs a massive investment of time and finance, and it is difficult to meet the facilities in general laboratories.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SCBC platform was further improved including the expansion of targets, higher throughput, more detection channels, and the simplification of structure . Recently, utilizing green fluorescent protein as a fluorescent, Salehi-Reyhani and colleagues developed an absolute quantification method for intracellular protein in single cells by stoichiometric analysis of single-molecule fluorescence images, and the abundance of a certain protein was determined according to calibrated standard curve . However, the reported microfluidic device-based single-cell analysis requires the professional design of channels, which needs a massive investment of time and finance, and it is difficult to meet the facilities in general laboratories.…”
mentioning
confidence: 99%
“…27 Recently, utilizing green fluorescent protein as a fluorescent, Salehi-Reyhani and colleagues developed an absolute quantification method for intracellular protein in single cells by stoichiometric analysis of single-molecule fluorescence images, and the abundance of a certain protein was determined according to calibrated standard curve. 28 However, the reported microfluidic device-based single-cell analysis requires the professional design of channels, which needs a massive investment of time and finance, and it is difficult to meet the facilities in general laboratories. Capillary-based technologies have been widely applied to various analyses and separation fields, standing out for simple, cost-effective, and modifiable superiority.…”
mentioning
confidence: 99%
“…One example is if the wavelength of the lysis beam overlaps that of a fluorophore’s absorption spectrum. There is no measurable photobleaching caused by the delivery of a pulse from the optical lysis laser (1064 nm) for fluorophores used here (Alexa Fluor 488, peak absorption 490 nm) . These results assume that the method of lysis is optimal and that GUV cargo is released fully into the aqueous solution of the analysis chamber and not retained within small unilamellar vesicles, therefore unavailable to bind to the sensing capture spot.…”
Section: Resultsmentioning
confidence: 79%
“…The proximity of the capture spot to the lysed GUV, the diameter of the spot, and the aspect ratio of the chamber (∼1:10 height to lateral width) all strongly promote interaction with the spot. We have recently shown that the method used here can faithfully and precisely measure the distribution of fluorescence proteins from biological cells, and the equivalence between the single-cell microarray and immunofluorescence data demonstrates how the former may be used to achieve accurate absolute quantification …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation